Harnessing mesenchymal aggregation for engineered organ‐level regeneration: Recent progress and perspective - Zheng, Chen‐Xi; Sui, Bing‐Dong; Jin, Yan (Aggregate (Hoboken), 2024)
Stem cells, especially mesenchymal progenitors or mesenchymal stem cells (MSCs), possess an intrinsic property to form compact spheroid‐like assemblies, a phenomenon known as cell aggregation. In recent years, a growing body of researches have uncovered that this is a cross‐species conserved developmental event essential for initiating organogenesis in a variety of organs. Moreover, the self‐assembly property also contributes to the regenerative capacities of MSC aggregates in vivo with broad range of applications in tissue engineering. In this review, the principles of self‐assembled mesenchymal aggregation and its involvement in physiological organogenesis, as well as the construction approaches of engineering MSC aggregates and its application for organ regeneration are discussed. The authors aim to provide a speculative overview of the current understanding and the recent findings of cell aggregation, from both the developmental and the engineering perspectives, and thus offer insights into the understanding of stem cell biology and the establishment of novel organ regeneration strategies. Mesenchymal aggregation is a cross‐species conserved developmental event important for organogenesis of multiple organs, which can be reconstituted and the resulting engineering constructs hold high potential for organ regeneration. This review summarizes the assembly principles of mesenchymal aggregation and its functions in physiological organogenesis, as well as the construction strategies of engineered mesenchymal aggregates and their application for organ regeneration.